Student teachers' manual for observation and participation - Corpuz, Brenda B; Rimas, Amparo T. ; Galangco, Norma Rika S.; Bautista, Apolinario G. (Quezon Avenue, Quezon City, 2002)
To put the student-teacher in the true spirit of student teaching, Part I of the manual sets the tone by giving every student teacher the opportunity to reflect on: (1) the raison d'etre of the course on Observation and Participation; (2) the work situation in which the student teacher will find himself/herself; (3) his/her level of readiness for the task at hand; and (4) on his/her own philosophy of education
Keywords: student teaching- handbook, manuals, etc; student teachers